Facile coprecipitation synthesis of nickel doped copper oxide nanocomposite as electrocatalyst for methanol electrooxidation in alkaline solution. (26th January 2018) - Arunachalam, Prabhakarn; Nagarani, S; Prasad, Saradh; AlSalhi, Mohamad S; Al-Mayouf, Abdullah M; Moydeen A, Meera; Ganapathy, Sasikala
Abstract: A nickel doped copper oxide (Ni–CuO) nanocomposite is prepared by the coprecipitation method for use as an electrocatalyst. The physicochemical properties of the synthesized electrocatalyst are characterized by powder XRD analysis, Fourier transform-infrared spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and N2 sorption measurements. The electrocatalytic performance of the Ni–CuO nanocomposite with respect to the electrochemical oxidation of methanol in an alkaline medium is evaluated through cyclic voltammetry and chronopotentiometry measurements. The reaction involving the electrooxidation of methanol is investigated comprehensively by varying experimental parameters such as the amount of catalyst used and the methanol solution concentration. The superior electrocatalytic activity of the Ni–CuO nanocomposite is attributable to its surface morphology and the presence of a large number of catalytically active sites on the nanocomposite surface. The results of this study suggest that the synthesized Ni–CuO nanocomposite should be suitable for use as an economical and abundant electrocatalyst in direct methanol fuel cells.